Analisis Bahaya Alami (Natural Hazards) Di Kecamatan Baleendah Kabupaten Bandung Jawa Barat: Natural Hazards Analysis in Baleendah District, Bandung Regency, West Java - Mazlan; Boedi Tjahjono; Baba Barus (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2020)
Flood disasters in Baleendah District (Bandung Regency) which occur every year often cause hundreds of hectares of paddy fields to fail in harvesting. Meanwhile, rapid land use changes occurred in the plain area has caused many paddy fields have turned into settlements, while many of slopes of hills area have turned into barelands caused by rock mining activities. This kind of activity can reduce slope stability and facilitate landslides in the future. Studying the natural hazards for this region becomes important for disaster mitigation needs in the future. The purpose of this study is to map land use and assess flood and landslide hazards in Baleendah District. The research method includes land use visual interpretation from Quickbird imagery, Pairwise Comparison analysis to obtain the weight and score of flood and landslide hazards parameters, and Multi Criteria Evaluation (MCE) analysis to assess the natural hazards. The results showed that the interpretation of Quickbird imagery produced 12 types of land use dominated by settlement types (31.17%) and rice fields (30.90%). From Pairwise Comparison analysis, it was found that the sequence of weights of flood hazard parameters were inundation duration (0.50), inundation frequency (0.33), and inundation depth (0.17), while for landslide hazards were slope steepness (0.50), land use (0.33), and slope form (0.17). Based on the participatory flood-prone mapping, it was found that flood-prone areas were only spread in one village, i.e. Andir Village, while for landslide-prone areas were spread in 5 villages. The results of Multi Criteria Evaluation (MCE) analysis showed that the high and medium class of flood hazards covered 128.99 ha and 34.76 ha respectively, while high, medium and low class of landslide hazards covered ​​281.62 ha, 940.84 ha and 124.69 ha respectively. Controlling land use change is a good choice to do in this region to reduce natural hazards in the future.